On some properties of convex functions - Stepanets, O. I.; Shydlich, A. L.; Степанець, О. І.; Шидліч, А. Л. (Institute of Mathematics, NAS of Ukraine, 2007)
We obtain some new results for convex-downward functions vanishing at infinity.